Performance and Intestinal Profiles of Tegal Duck Fed Ration Supplemented with Prebiotics - N. Iriyanti; B. Hartoyo; S. Suhermiyati (Faculty of Animal Science, Bogor Agricultural University, 2018)
This research was aimed to determine the effects of prebiotics on performance and gastrointestinal profiles of Tegal ducks. One hundred two-month-old male Tegal ducks were distributed into 5 treatment groups; R0= control; R1= FOS; R2= MOS; R3= Inulin; and R4= natural prebiotic (water hyacinth/Eichhornia crassipes). The prebiotics were given at 0.2% of the total feed (w/w). The observed variables were performances and gastrointestinal profiles. This study used a completely randomized design and continued with honestly significant difference test. Performance (live weight, body weight gain, and feed intake) and intestinal profile (percentage weights of intestine, gizzard, crop, and pancreas) of ducks were not significantly affected by prebiotic supplementation in feed. FOS prebiotic and natural prebiotic from water hyacinth showed increased (P<0.05) the percentage of carcass and cecum weight compared to the other treatments. In conclusion, the use of different prebiotics resulted in relatively similar performances and digestive tract profiles except the percentage of carcass and cecum weight that increased by 4.5% and 36.67%, respectively, with the supplementation of either FOS or water hyacinth.